Preparation of Lu₂O₃:Eu³⁺ nanopowders for optical ceramics - Yavetskiy, R.P. (Functional Materials, 2008)
The Lu₂O₃:Eu³⁺ (1 at. (Yo) nanopowders have been obtained by precipitation from aqueous solution using ammonium hydrocarbonate as the precipitant. The influence of the calcination temperature on the morphology, average particle size and sinterability of Lu₂O₃:Eu³⁺powders have been studied. It has been shown that the calcination temperature of 1000°C provides the preparation of low-agglomerated fine powders of europium doped lutetium oxide with spherical particles and high surface activity that can be used as a starting material for transparent ceramics manufacturing.